Network-Related Changes in Neurotransmitters and Seizure Propagation During Rodent Epileptogenesis. (4th May 2021) - Dhaher, Roni; Gruenbaum, Shaun E.; Sandhu, Mani Ratnesh S.; Ottestad-Hansen, Sigrid; Tu, Nathan; Wang, Yue; Lee, Tih-Shih W.; Deshpande, Ketaki; Spencer, Dennis D.; Danbolt, Niels Christian; Zaveri, Hitten P.; Eid, Tore
Abstract : Objective: To test the hypothesis that glutamate and GABA are linked to the formation of epilepsy networks and the triggering of spontaneous seizures, we examined seizure initiation/propagation characteristics and neurotransmitter levels during epileptogenesis in a translationally relevant rodent model of mesial temporal lobe epilepsy. Methods: The glutamine synthetase (GS) inhibitor methionine sulfoximine was infused into one of the hippocampi in laboratory rats to create a seizure focus. Long-term video-intracranial EEG recordings and brain microdialysis combined with mass spectrometry were used to examine seizure initiation, seizure propagation, and extracellular brain levels of glutamate and GABA. Results: All seizures (n = 78 seizures, n = 3 rats) appeared first in the GS-inhibited hippocampus of all animals, followed by propagation to the contralateral hippocampus. Propagation time decreased significantly from 11.65 seconds early in epileptogenesis (weeks 1–2) to 6.82 seconds late in epileptogenesis (weeks 3–4, paired t test, p = 0.025). Baseline extracellular glutamate levels were 11.6-fold higher in the hippocampus of seizure propagation (7.3 µM) vs the hippocampus of seizure onset (0.63 µM, analysis of variance/Fisher least significant difference, p = 0.01), even though the concentrations of the major glutamate transporter proteins excitatory amino acid transporter subtypes 1 and 2 and xCT were unchanged between the brain regions. Finally, extracellular GABA in the seizure focus decreased significantly from baseline several hours before a spontaneous seizure (paired t test/false discovery rate). Conclusion: The changes in glutamate and GABA suggest novel and potentially important roles of the amino acids in epilepsy network formation and in the initiation and propagation of spontaneous seizures.